2014
DOI: 10.1063/1.4862226
|View full text |Cite
|
Sign up to set email alerts
|

Wave-function engineering and absorption spectra in Si0.16Ge0.84/Ge0.94Sn0.06/Si0.16Ge0.84 strained on relaxed Si0.10Ge0.90 type I quantum well

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The analytical expressions are quoted as follows in eV: It is found that the pseudomorphic Ge 1-x Sn x /Ge (001) alloys show an L-indirect to Γ direct band gap transition at Sn-fraction at 15.3% at room temperature. It is worth to note that for the relaxed Ge 1-x Sn x alloys, the indirect-todirect crossover was taken for Sn-fraction of 5.7% at room temperature [25]. The latter values are consistent with the experimental crossover found at about 17% and 6.3% respectively for temperatures around 10 K in Ref [17].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The analytical expressions are quoted as follows in eV: It is found that the pseudomorphic Ge 1-x Sn x /Ge (001) alloys show an L-indirect to Γ direct band gap transition at Sn-fraction at 15.3% at room temperature. It is worth to note that for the relaxed Ge 1-x Sn x alloys, the indirect-todirect crossover was taken for Sn-fraction of 5.7% at room temperature [25]. The latter values are consistent with the experimental crossover found at about 17% and 6.3% respectively for temperatures around 10 K in Ref [17].…”
Section: Introductionmentioning
confidence: 71%
“…From this preliminary and mendatory work, we conclude that pseudomorphic Ge 1-x Sn x alloys become direct band gap semiconductors at a Sn-fraction of 15 [19,20], Ge on insulator (GeOI) substrates formed by wafer bounding [21][22][23] or recent advances in the growth of germanium nanowire arrays by vapour-liquid-solid (VLS) and vapoursolid-solid (VSS) techniques [24]. In this work and on the basis of our previous results [25] on the electronic band parameters for GeSn strained, first we determined the band offsets at Ge 1−x Sn x /Ge strained (001)-oriented relaxed interfaces. Then, we investigate the quantum levels and wave functions of the designed double Ge/Ge 0.92 Sn 0.08 /Ge QWs.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…x Sn x is taken from our calculations in [21]. All the other parameters for the Ge 1−x Sn x material systems are calculated using a simple linear interpolation between Ge, and α-Sn, whose values are taken form references [22][23][24] …”
Section: Calculation Of Materials Parametersmentioning
confidence: 99%
“…The device is sketched in figure 2. The material parameters used are taken from [23][24][25] and summarized in table 2. The compressive lattice mismatch between Ge 0.964 Sn 0.036 and Ge is 0.52% while the average mismatch of the 200 nm-thick stacks is 0.26%.…”
Section: Studied Structure and Modelingmentioning
confidence: 99%